Opportunities and challenges for community involvement in public service provision in rural Guatemala - Speer, Johanna; Vásquez, William F. (International Food Policy Research Institute, 2013)
The purpose of the research summarized in this paper is to provide policy-relevant knowledge on the governance of rural services in Guatemala and thus to contribute to improving the provision of services that are essential for agricultural and rural development. Based on quantitative and qualitative primary data, we examine how services are actually provided today and how community preferences and participation affect service provision in rural Guatemala. Our main finding is that the provision of formally decentralized services by local governments is incomplete.